5.2.41 Problems 4001 to 4100

Table 5.249: Second order linear ODE

#

ODE

Mathematica

Maple

14093

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = {\mathrm e}^{t} \]

14094

\[ {}y^{\prime \prime }-3 y^{\prime }-7 y = 4 \]

14096

\[ {}3 y^{\prime \prime }+5 y^{\prime }-2 y = 3 t^{2} \]

14130

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

14131

\[ {}x y^{\prime \prime }+2 y^{\prime }+x y = 0 \]

14132

\[ {}y^{\prime \prime }-2 y^{\prime }+y = x^{{3}/{2}} {\mathrm e}^{x} \]

14133

\[ {}y^{\prime \prime }+4 y = 2 \sec \left (2 x \right ) \]

14134

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{x}+\left (1-\frac {1}{4 x^{2}}\right ) y = x \]

14135

\[ {}y^{\prime \prime }+y = f \left (x \right ) \]

14136

\[ {}x^{2} y^{\prime \prime }+x \left (x -\frac {1}{2}\right ) y^{\prime }+\frac {y}{2} = 0 \]

14137

\[ {}x^{2} y^{\prime \prime }+x \left (1+x \right ) y^{\prime }-y = 0 \]

14146

\[ {}y^{\prime \prime }-x^{2} y = 0 \]

14147

\[ {}x y^{\prime \prime }+y^{\prime }+y = 0 \]

14148

\[ {}x y^{\prime \prime }+x^{2} y = 0 \]

14149

\[ {}y^{\prime \prime }+\alpha ^{2} y = 0 \]

14150

\[ {}y^{\prime \prime }-\alpha ^{2} y = 0 \]

14151

\[ {}y^{\prime \prime }+\beta y^{\prime }+\gamma y = 0 \]

14152

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+n \left (n +1\right ) y = 0 \]

14153

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (-\nu ^{2}+x^{2}\right ) y = \sin \left (x \right ) \]

14159

\[ {}y^{\prime \prime }-2 k y^{\prime }+k^{2} y = {\mathrm e}^{x} \]

14160

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }-a^{2} y = 0 \]

14161

\[ {}y^{\prime \prime }+\frac {2 y^{\prime }}{x} = 0 \]

14228

\[ {}y^{\prime \prime } = a^{2} y \]

14230

\[ {}x y^{\prime \prime }-y^{\prime } = {\mathrm e}^{x} x^{2} \]

14232

\[ {}y^{\prime \prime }+\tan \left (x \right ) y^{\prime } = \sin \left (2 x \right ) \]

14237

\[ {}y^{\prime \prime } = 9 y \]

14238

\[ {}y^{\prime \prime }+y = 0 \]

14239

\[ {}y^{\prime \prime }-y = 0 \]

14240

\[ {}y^{\prime \prime }+12 y = 7 y^{\prime } \]

14241

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

14242

\[ {}y^{\prime \prime }+2 y^{\prime }+10 y = 0 \]

14243

\[ {}y^{\prime \prime }+3 y^{\prime }-2 y = 0 \]

14244

\[ {}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0 \]

14245

\[ {}y^{\prime \prime }+y^{\prime }+y = 0 \]

14254

\[ {}y^{\prime \prime }-7 y^{\prime }+12 y = x \]

14255

\[ {}s^{\prime \prime }-a^{2} s = t +1 \]

14256

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 8 \sin \left (2 x \right ) \]

14257

\[ {}y^{\prime \prime }-y = 5 x +2 \]

14258

\[ {}y^{\prime \prime }-2 a y^{\prime }+a^{2} y = {\mathrm e}^{x} \]

14259

\[ {}y^{\prime \prime }+6 y^{\prime }+5 y = {\mathrm e}^{2 x} \]

14260

\[ {}y^{\prime \prime }+9 y = 6 \,{\mathrm e}^{3 x} \]

14261

\[ {}y^{\prime \prime }-3 y^{\prime } = 2-6 x \]

14262

\[ {}y^{\prime \prime }-2 y^{\prime }+3 y = {\mathrm e}^{-x} \cos \left (x \right ) \]

14263

\[ {}y^{\prime \prime }+4 y = 2 \sin \left (2 x \right ) \]

14267

\[ {}y^{\prime \prime }+2 h y^{\prime }+n^{2} y = 0 \]

14268

\[ {}y^{\prime \prime }+n^{2} y = h \sin \left (r x \right ) \]

14269

\[ {}y^{\prime \prime }-7 y^{\prime }+6 y = \sin \left (x \right ) \]

14270

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \]

14271

\[ {}y^{\prime \prime }+y = \frac {1}{\cos \left (2 x \right )^{{3}/{2}}} \]

14278

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \]

14281

\[ {}y^{\prime \prime }-4 y = {\mathrm e}^{2 x} \sin \left (2 x \right ) \]

14310

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-y = 0 \]

14312

\[ {}2 x^{2} y^{\prime \prime }+3 x y^{\prime }-y = 0 \]

14313

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

14314

\[ {}x^{2} y^{\prime \prime }-2 y = 0 \]

14320

\[ {}2 x^{2} y^{\prime \prime }+x y^{\prime }-y = 0 \]

14323

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = 0 \]

14324

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

14327

\[ {}x^{2} y^{\prime \prime }-x y^{\prime } = 0 \]

14328

\[ {}x^{2} y^{\prime \prime }+6 x y^{\prime }+4 y = 0 \]

14329

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+9 y = 0 \]

14335

\[ {}y^{\prime \prime }-y^{\prime }-6 y = 0 \]

14337

\[ {}y^{\prime \prime }-y = 0 \]

14340

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 0 \]

14341

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 0 \]

14342

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 0 \]

14343

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 0 \]

14345

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0 \]

14346

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0 \]

14347

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0 \]

14348

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0 \]

14349

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0 \]

14350

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0 \]

14480

\[ {}3 y^{\prime \prime }-2 y^{\prime }+4 y = x \]

14482

\[ {}x \left (x -3\right ) y^{\prime \prime }+3 y^{\prime } = x^{2} \]

14483

\[ {}x \left (x -3\right ) y^{\prime \prime }+3 y^{\prime } = x^{2} \]

14484

\[ {}\sqrt {1-x}\, y^{\prime \prime }-4 y = \sin \left (x \right ) \]

14485

\[ {}\left (x^{2}-4\right ) y^{\prime \prime }+y \ln \left (x \right ) = x \,{\mathrm e}^{x} \]

14486

\[ {}y^{\prime \prime }-y = 0 \]

14487

\[ {}y^{\prime \prime }+y = 0 \]

14488

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-2 y = 0 \]

14490

\[ {}y^{\prime \prime }-y = 0 \]

14492

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+y = 0 \]

14493

\[ {}y^{\prime \prime }-4 y = 31 \]

14494

\[ {}y^{\prime \prime }+9 y = 27 x +18 \]

14495

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = -3 x -\frac {3}{x} \]

14496

\[ {}4 y^{\prime \prime }+4 y^{\prime }-3 y = 0 \]

14506

\[ {}y^{\prime \prime }+\alpha y = 0 \]

14522

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 0 \]

14524

\[ {}y^{\prime \prime }-9 y = 2 \sin \left (3 x \right ) \]

14525

\[ {}y^{\prime \prime }+9 y = 2 \sin \left (3 x \right ) \]

14526

\[ {}y^{\prime \prime }+y^{\prime }-2 y = x \,{\mathrm e}^{x}-3 x^{2} \]

14530

\[ {}y^{\prime \prime }-9 y = x +2 \]

14531

\[ {}y^{\prime \prime }+9 y = x +2 \]

14532

\[ {}y^{\prime \prime }-y^{\prime }+6 y = -2 \sin \left (3 x \right ) \]

14533

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = -x^{2}+1 \]

14537

\[ {}y^{\prime \prime }+9 y = 1 \]

14538

\[ {}y^{\prime \prime }+9 y = 18 \,{\mathrm e}^{3 x} \]

14539

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 0 \]

14540

\[ {}y^{\prime \prime }-y^{\prime }-2 y = x^{2} \]